Spatio-Temporal Assessment of Zooplankton Fauna of Uta Ewa Estuary, Akwa Ibom State, Nigeria. - Udeme Effiong Jonah; Emeka Donald Anyanwu; Diane Akudo Avoaja (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
Estuaries are influenced by the mixture of river water with seawater; creating unique ecosystems with several physical and chemical processes affecting the water quality. Spatial and temporal assessment of the composition, abundance, and distribution of zooplankton fauna of Uta Ewa Estuarine water system was carried out between May 2019 and February 2020 to assess the effects of anthropogenic activities on the zooplankton assemblage. Water and Zooplankton samples were collected from three (3) stations using standard procedures. Some parameters like water temperature, dissolved oxygen, hydrogen-ion, electrical conductivity, and turbidity were determined in-situ. The ranges of the physico-chemical parameters were: water temperature (24.9-25.3oC), EC (62.3-70.9mS/m), pH (6.5-6.7), turbidity (12.0-28.0NTU), DO (3.8-4.7mg/L), BOD (2.3-3.2mg/L), phosphate (3.2-5.2mg/L), and nitrate (3.0-6.3mg/L). ANOVA showed a significant difference (p<0.05) in the spatial and temporal means values of some parameters. A total of 1,067 individuals from 30 zooplankton taxa and 4 taxonomic groups were recorded. Rotifers (33.4%) were the dominant group, followed by protozoa (32.9%), copepods (20.9%) and cladocerans (13.8%). Station 1 had the highest abundance (388 individuals), station 2 (303 individuals) and station 3(375 individuals). The higher number of individuals (193) was recorded in August 2019. The biodiversity indices pointed to slightly polluted to stable environment. This study showed that the water quality and zooplankton community was influenced by anthropogenic activities both spatially and temporally but season also played a major role in the temporal variation. In conclusion, the water quality was deteriorating due to anthropogenic activities, which in turn affected the structure of zooplankton community. Keywords: Abundance, Assessment, Zooplankton, Physicochemical, Estuary